The Rock Garden - Royal Botanic Gardens, Port of Spain, Trinidad, B.W.I. - Dalla Costa, H. (Y. De Lima and Co. Ltd., Trinidad, 2009)
In the foreground are the Rock Gardens, located in the north western corner of the Queen's Park Savannah, close to the Emperor Valley Zoo and Botanical Gardens and in the background at right, part of Stollmeyer's Castle can be seen.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Rock gardens--Trinidad and Tobago; Local term--Magnificent Seven (The) - Port of Spain; [1960]; Outdoor recreation--Trinidad and Tobago; Plants--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Trees--Trinidad and Tobago; Women--Trinidad and Tobago; Leisure--Trinidad and Tobago; Recreation--Trinidad and Tobago; Architecture--Trinidad and Tobago; Castles--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Mansions--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Queen's Park Savannah (Port of Spain); Magnificent Seven, The (Port of Spain); Stollmeyer's Castle (Port of Spain)